2015
DOI: 10.1002/pbc.25552
|View full text |Cite
|
Sign up to set email alerts
|

Genetic abnormalities in adolescents and young adults with neuroblastoma: A report from the Italian Neuroblastoma Group

Abstract: This study confirmed the low incidence of MYCN amplification in AYA and recorded a high frequency of 17q gain and 9p and 11q loss independently from the stage of the disease. The presence of 1q gain, which identifies patients with particularly aggressive disease, relapse and poor survival, was also detected. Furthermore, the frequency of ALK mutations suggests that a target-based therapy with ALK inhibitors might be effective in this subset of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 37 publications
5
33
1
5
Order By: Relevance
“…Similar to other reports on adult-onset NB 7, 18, 19, 21 , none of our patients had MYCN -amplified NB. (Table 1) This is in contrast to pediatric NB where 20–25% of patients have MYCN -amplified NB 5, 22 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to other reports on adult-onset NB 7, 18, 19, 21 , none of our patients had MYCN -amplified NB. (Table 1) This is in contrast to pediatric NB where 20–25% of patients have MYCN -amplified NB 5, 22 .…”
Section: Discussionsupporting
confidence: 92%
“…Pediatric solid tumors in general, and NB in particular have a low frequency of mutations, 38 but genetic testing on tumors in adults yielded a significantly different pattern of genomic aberrations. Similar to other reports on adult-onset NB, 7,18,19,21 none of our patients had MYCN-amplified NB ( Table 1). This is in contrast to pediatric NB where 20-25% of patients have MYCN-amplified NB.…”
Section: Discussionsupporting
confidence: 92%
“…Our gain-and loss-of-function studies indicated that CUX1 promoted the aerobic glycolysis, growth, and invasiveness of NB cells, suggesting its oncogenic roles in NB progression. Human CUX1 gene locates at chromosome 7q22, a region associated with copy number gain that contributes to multidrug resistance in NB (Mazzocco et al, 2015). However, we found no alteration of copy number or genetic variants of CUX1 in NB cohorts, indicating other mechanisms facilitating its over-expression.…”
Section: Discussioncontrasting
confidence: 57%
“…Human CUX1 gene locates at chromosome 7q22, a region associated with copy number gain that contributes to multidrug resistance in NB (Mazzocco et al , ). However, we found no alteration of copy number or genetic variants of CUX1 in NB cohorts, indicating other mechanisms facilitating its over‐expression.…”
Section: Discussionmentioning
confidence: 99%
“…In the particular subgroup of NBs occurring in adolescent and young adults [30], representing less than 5% of NBs and characterized by a high prevalence of SCA (35–85%) and very low incidence of MNA, the prevalence of 11q loss is high, ranging between 30 to 60% [3739]. In this particular subgroup where ALK and ATRX alterations are also more frequent and the outcome very poor [3740], ATRX mutated NBs showed a higher number of SCA including 11q deletions (Fig.…”
Section: Introductionmentioning
confidence: 99%